Who Gets Debt Relief? - Chauvin, Nicolas Depetris; Kraay, Aart (World Bank, Washington, DC, 2012)
The authors use preliminary results from an ongoing effort to construct estimates of debt relief to study its allocation across a sample of 62 low-income countries. They find some evidence that debt relief, particularly from multilateral creditors, has been allocated to countries with better policies in recent years. Somewhat surprisingly, conditional on per capita incomes and policy, more indebted countries are not much more likely to receive debt relief. But countries that have large debts especially to multilateral creditors are more likely to receive debt relief. The authors do not find much evidence that debt relief responds to shocks to GDP growth. Finally, most of the persistence in debt relief is driven by slowly changing country characteristics, indicating that it may be difficult for countries to "exit" from cycles of repeated debt relief.